Tobacco mosaic virus for the targeted delivery of drugs to cells expressing prostate-specific membrane antigen. Issue 33 (6th June 2021) - Shukla, Sourabh; Marks, Isaac; Church, Derek; Chan, Soo-Khim; Pokorski, Jonathan K.; Steinmetz, Nicole F.
Abstract : Prostate-specific membrane antigen (PSMA) is a membrane-bound protein that is preferentially expressed in the prostate gland and induced in many prostate cancers, making it an important target for new diagnostics and therapeutics. Abstract : Prostate-specific membrane antigen (PSMA) is a membrane-bound protein that is preferentially expressed in the prostate gland and induced in many prostate cancers, making it an important target for new diagnostics and therapeutics. To improve the efficacy of nanoparticle formulations for the imaging and/or eradication of prostate cancer, we synthesized the PSMA-binding glutamic acid derivative DUPA and conjugated it to the external surface of tobacco mosaic virus (TMV) particles. DUPA-targeted TMV was subsequently loaded with the antineoplastic agent mitoxantrone (MTO) or conjugated internally with the fluorescent dye cyanine 5 (Cy5). We found that TMV particles could be efficiently decorated with DUPA and loaded with MTO or Cy5 while maintaining structural integrity. DUPA-targeted TMV particles were able to bind more efficiently to the surface of PSMA + LNCaP cells compared to non-targeted TMV; but there was little difference in binding efficiency between targeted and untargeted TMV when we tested PSMA − PC3 cells (both cell lines are prostate cancer cell lines). DUPA-targeted TMV particles were internalized by LNCaP cells enabling drug delivery. Finally, we loaded the DUPA-targeted TMV particles and untargeted control particles with MTO to test their cytotoxicity against LNCaP cells in vitro . The cytotoxicity of the TMV-MTO particles (IC50 = 10.2 nM) did not differ significantly from that of soluble MTO at an equivalent dose (IC50 = 12.5 nM) but the targeted particles (TMV-DUPA-MTO) were much more potent (IC50 = 2.80 nM). The threefold increase in cytotoxicity conferred by the DUPA ligand suggests that MTO-loaded, DUPA-coated TMV particles are promising as a therapeutic strategy for PSMA + prostate cancer and should be advanced to preclinical testing in mouse models of prostate cancer.